Influential Article Review - A Theoretical Model for the Explanation of Innovation - Jones, Cindy; Wheeler, Bobby; Santos, Freda (Journal of Strategic Innovation and Sustainability, 2019)
This paper examines innovation. We present insights from a highly influential paper. Here are the highlights from this paper: The aim of this paper is to transfer the innovation system (IS) approach to the microeconomic level, creating a conceptual framework which helps individual actors to explain, identify, and predict the origin of innovations. Based on the ongoing discussion about the applicability of boundedly rational search and, in particular, the metaphor of an opportunity landscape, the author has developed a conceptual framework for the origin of economic innovations, structured along three dimensions. First, the adjacent possibility defines a narrow space of potential first-order combinations of existing knowledge, which is the trajectory for the new developments in technology and science. Second, the adjacent possibility defines an area of expected cost reduction which enables the exploitation of the new technologies within a threshold. Finally, the adjacent acceptable represents a small area on the current edges of socially accepted behavior, which currently only innovators embrace, but soon will reach the early majority of adopters. It is, however, the moment when all three dimensions achieve an intersecting area, when the opportunity vacuum (OV) is created. The OV is a space, which strongly attracts innovation and often creates multiple inventions at the same time emerging independently. While this model is aimed at explaining the origin of economic innovations in retrospective, it can also be applied as a framing method to anticipate future economic novelty. For our overseas readers, we then present the insights from this paper in Spanish, French, Portuguese, and German.